Migration-Based Moth-Flame Optimization Algorithm; Processes; Vol. 9, iss. 12 - Nadimi-Shahraki M. H. Mohammad; Fatahi A. Ali; Zamani H. Hoda; Mirjalili S. Seyedali; Abualigah L. Laith; Mokhamed Elsaed (Mohamed Abd Elaziz) A. M. Akhmed Mokhamed (2021, 2021)
Title screen